1994
DOI: 10.1177/002221949402700606
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Lead and Specific Attentional Problems in Schoolchildren

Abstract: A pilot study was carried out to investigate the relationship between exposure to lead and attention in children. The participants were 43 boys, 8 to 12 years of age, attending special schools for children with educational and/or learning problems (so called LOM schools). Children with probable causes of attentional or memory problems other than lead contamination were excluded from the study. Various aspects of attention were measured using neuropsychological tests. As an assessment of body lead burden, lead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 14 publications
0
18
0
3
Order By: Relevance
“…In the United States, regulation has reduced the incidence of lead poisoning to < 4%, but low-level exposure early in development remains common even in the United States (12). Blood lead levels from 1 to 10 μg/dL are associated with lower child intelligence quotient (IQ; 13), weaker executive cognitive abilities (14,15), behavioral symptoms of ADHD (16)(17)(18), and diagnosis of ADHD (19,20) in community surveys. Early studies (18)(19)(20) confirmed that blood lead was associated with clinical ADHD even after control for numerous confounders although generally at lead levels higher than typical today (i.e., 10-20 μg/dL vs. the current population average in US children of 1-2 μg/dL) (21).…”
mentioning
confidence: 99%
“…In the United States, regulation has reduced the incidence of lead poisoning to < 4%, but low-level exposure early in development remains common even in the United States (12). Blood lead levels from 1 to 10 μg/dL are associated with lower child intelligence quotient (IQ; 13), weaker executive cognitive abilities (14,15), behavioral symptoms of ADHD (16)(17)(18), and diagnosis of ADHD (19,20) in community surveys. Early studies (18)(19)(20) confirmed that blood lead was associated with clinical ADHD even after control for numerous confounders although generally at lead levels higher than typical today (i.e., 10-20 μg/dL vs. the current population average in US children of 1-2 μg/dL) (21).…”
mentioning
confidence: 99%
“…Abnormalities in the midbrain DA system are highly suspect in the etiology of attention-deficit hyperactivity disorder (Sagvolden and Sergeant, 1998;Solanto, 2002;DiMaio et al, 2003;Krause et al, 2003). Although the etiology of attention-deficit hyperactivity disorder (ADHD) is likely multifactorial (Davids et al, 2003;DiMaio et al, 2003), evidence suggests that lead exposure is a risk factor for the development of ADHD in an exposed subpopulation of ADHD patients (Minder et al, 1994;Tuthill, 1996;Canfield et al, 2003b). However, the precise nature of the effects of lead on attention mechanisms, and the degree to which lead-induced attention deficits contribute to impaired learning, is a matter still under investigation (Cory-Slechta, 2003).…”
mentioning
confidence: 99%
“…Lead School children (ADHD, learning disabilities) Fergusson and Horwood 1993;Lyngbye et al 1990;Tong et al 1996;Tuthill 1996;Leviton et al 1993;Minder et al 1994;Buchanan et al 1999;al-Saleh et al 2001;Lanphear et al 2005;McMichael et al 1988;Canfield et al 2003;Chiodo et al 2007;Counter et al 2008;Nigg et al 2008;Schnaas et al 2006;Wang et al 2002;Wang et al 2008 Marshall et al 1995;Jackson 1996 Lassen andOei 1998;Rowland et al 2002;Batstra et al 2003;Najman et al 2004;O'Brien et al 2004;Matsumoto et al 2005 Table 2. Literature lists for the hazard effects of ECSs on human memory and cognition.…”
Section: Chemicals Study Type/hazard Effects Referencesmentioning
confidence: 99%